Uma solução para execução de aplicações Ginga-ncl usando segunda tela em sistemas Broad Band TV - Guedes, álan Livio Vasconcelos (2012)
On the development of applications for Digital the TV environment Ginga-NCL provides application support with use of second screen devices. However, it was only in fact made possible by recent efforts in the implementation of the Ginga-NCL reference using a strategy o association between UAProf profiles and the required devices. This work proposes architecture of Broadband TV Application Store that uses the Ginga-NCL, being able to present to user a list of compatible applications to their multidevice execution context. As results, are presented a description of the architecture and execution of tests with prototypes of software.